ANALISIS KINERJA SMA NEGERI 1 PEKANBARU MENGGUNAKAN METODE BALANCE SCORECARD - Roza Sri Susanti; Gusnardi Gusnardi; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The study is aimed at describing the performance of educational institutions using Balance ScoreCard method which is applied at SMA Negeri 1 Pekanbaru. SMA Negeri 1 Pekanbaru is one of the leading schools with a lot of achievements in the field of academic and non academic. An educational institution can not be said to excel as a whole if it is only assessed by its achievement, because in educational institutions, not only the components of achievement are noticed but are also many components which have connection one to another.This research uses data analysis mix method technique with analisis unit 91 students and 51 staffs including teachers, education staffs and non permanent workers .Based on the four perspectives contained in the method of Balance Score Card (i.e financial perspective, customer, internal business and growth and learning), SMA Negeri 1 Pekanbaru performance is then categorized very well.Key Words: School Perfomance, Balance Scorecard.